Anti-psoriatic characteristics of ROCEN (topical Arthrocen) in comparison with Cyclosporine A in a murine model - Ramin Goudarzi; Min-Ho Kim; Alireza Partoazar (BMC, 2024)
Abstract Topical ROCEN (Roc), liposomal arthrocen hydrogel, is a robust anti-inflammatory formulation which has been developed for skin diseases such as eczema. Therefore, we aimed to evaluate the efficacy of Roc 2% on the healing of imiquimod (Imiq)-induced psoriasis in a mouse model. Psoriasis was induced by applying Imiq topically to the mice's back skin once daily for five consecutive days. Moreover, a group of animal experiments was treated with Cyclosporine A (CsA), as a standard drug, for comparison with Roc treated group. The efficacy of Roc on skin lesions was evaluated by employing Psoriasis Area and Severity Index (PASI) scores. Subsequently, the skin samples were assessed using Baker's scoring system and Masson's trichrome staining, immunohistochemistry, and real-time PCR analysis. The observational and histopathological results indicated that topical application of Roc significantly reduced the PASI and Baker's scores in the plaque-type psoriasis model. Moreover, biochemical assessments showed that Roc suppressed significantly the increase of IL-17, IL-23, and TNF-α cytokines gene expression in the lesion site of psoriatic animals. In conclusion topical Roc 2% could significantly alleviate major pathological aspects of Imiq-induced psoriasis through inflammation inhibition which was comparable to the CsA drug. The beneficial outcomes of Roc application in the psoriasis model suggest its potential usage in complementary medicine.